(untitled) (Global Journal of Science Frontier Research, 2012)
Hymenoptera is one of the most diverse orders of insects, including over 115,000 described species. Some are phytophagous (plant-feeding), while others are herbivorous, predatory, or even parasitic. Hymenoptera distribution is often dependent on their food supply for eg., bees pollinate flowers and require habitats with flowering plants. Hymenoptera are important to the balancing and functioning of most ecosystems on the planet. These are also one of the most beneficial insects for the human economy. Not only do bees pollinate many of our crops, but they also produce goods such as wax any honey. Parasitic wasps are often the most successful way to control pest insects as biological control agents. The present study was therefore planned to observe and document hymenopteran pollinators existing in the vicinity of Bikaner (Rajasthan) and to monitor some of their activities. Thirteen species of hymenopterans belonging to seven families were found to visit the flowers of various crops cultivated in the agro-ecosystem during the present study. Maximum floral visitors (13 spp. belonging to 7 families) were documented on marigold, followed by mustard (9 spp. belonging to 5 families), ridged gourd (7 spp. belonging to 5 families), bottle gourd (6 spp. belonging to 4 families), brinjal (4 spp. belonging to 2 families), pumpkin (3 spp. belonging to 3 families), radish (5 spp. belonging to 3 families). Most number of hymenopteran species were documented during the month of January (12) followed by December (10), February (10), November (9), September (8) and October (7).The major hymenopteran visitors observed during the present study were Apis mellifera, Scolia specifica and Xylocopa fenestreta.